Influence of Digital Financial Education and Peer Recommendations on Mutual Fund Purchase Intention: The Mediating Role of Perceived Usefulness - Lenta, F. Josephine; Kumar, J. (International Review of Management and Marketing, 2026)
The present study investigates the determinants of investment intention of retail investors in mutual funds using online modes. Peers' recommendation (PR) direct effects on mutual fund buying intention and digital financial education (DFE) direct effects are investigated, along with the mediating role of perceived usefulness (PU). Data was collected from 340 respondents and SmartPLS 4's Partial Least Squares Structural Equation Modelling (PLS-SEM) was used for the analysis. The results show that both PRs and DFE significantly increase purchase intent, both directly and indirectly through PU. According to the study, PU plays a cognitive mediating role in converting external information into investment intentions. These observations complement the literature on digital adoption and behavioural finance, while also offering practical implications for FinTech platforms and policymakers aiming to promote mutual fund adoption and financial literacy among emerging investors.